1990
DOI: 10.1002/eji.1830200234
|View full text |Cite
|
Sign up to set email alerts
|

Exit of recirculating lymphocytes from lymph nodes is directed by specific exit signals

Abstract: During recirculation, lymphocytes leave the peculiar structurally inverted lymph nodes (LN) of pigs via blood vessels instead of via efferent lymphatics, as in sheep and other mammals. This functional difference provided an opportunity to show the existence of signals directing lymphocyte exit from LN. The recirculation of pig peripheral blood lymphocytes was traced through fetal sheep LN and of sheep PBL into and out of unsuckled newborn piglet LN, using the lack of natural antibody or natural killer cell fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

1991
1991
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 15 publications
0
4
1
Order By: Relevance
“…Fetal sheep of this age lack natural antibodies or natural killer (NK) cell activity and have been used as a model to examine xenogeneic lymphocyte recirculation. 15 Our results show that gut-homing receptors are acquired extrathymically, although they do not exclude the possibility that the postnatal thymus may also export T cells with the ability to home to gut. It thus appears that the development of tissue-specific homing of T cells to gut is different from skin and peripheral nodes.…”
Section: Discussioncontrasting
confidence: 78%
“…Fetal sheep of this age lack natural antibodies or natural killer (NK) cell activity and have been used as a model to examine xenogeneic lymphocyte recirculation. 15 Our results show that gut-homing receptors are acquired extrathymically, although they do not exclude the possibility that the postnatal thymus may also export T cells with the ability to home to gut. It thus appears that the development of tissue-specific homing of T cells to gut is different from skin and peripheral nodes.…”
Section: Discussioncontrasting
confidence: 78%
“…It has long been appreciated that lymphocyte exit into the efferent lymph is not a random event [54]. Identifying the drivers of the global, unspecific lymphoid organ shutdown will pave the way for better understanding its physiological consequences, possibly including enhanced encounter of antigen by naïve T cells, promotion of memory formation of responding lymphocytes and barrier functions to contain infectious agents on site.…”
Section: Discussionmentioning
confidence: 99%
“…If little is known regarding the migration of cells through tissues, comparatively less is known regarding their entry into lymphatics. It is unclear as to whether the entry of lymphocytes into lymphatics is an active or a passive process, but it has been demonstrated that specific exit signals govern the migration of lymphocytes out of lymph nodes (35)(36)(37). Although recent studies have indicated that lymphatic endothelial cells may express some chemokines related to lymphocyte recruitment, their role in regulating the entry of cells into lymph remain unclear (33).…”
Section: Discussionmentioning
confidence: 99%